Pediatric Cutaneous Hematologic Disorders: Cutaneous Lymphoma and Leukemia Cutis—Experience of a Tertiary-Care Pediatric Institution and Review of the Literature. Issue 4 (July 2022) - Colmant, Caroline; Demers, Marc-André; Hatami, Afshin; Coulombe, Jerome; McCuaig, Catherine Cameron; Piram, Maryam; Marcoux, Danielle; Kokta, Victor; Powell, Julie
Background: Cutaneous hematologic malignancies are rare in children, and the literature about them is still sparse. Objective: The purpose of our study was to report our experience with pediatric cases of cutaneous hematologic disorders and describe their clinical and histological features. Methods: Data were retrospectively collected from the histopathologic database of the CHU Sainte-Justine, University of Montreal, Montreal, Canada. All patients up to 18 years of age with a diagnosis of a primary cutaneous lymphoma (including lymphomatoid papulosis), secondary cutaneous lymphoma or cutaneous manifestations of leukemia, followed from 1980 to 2019 at our center were reviewed. Results: Thirty-six patients were included. Age at presentation ranged from birth to 18 years of age (mean 7.83 ± 5.16; median 7.0). Ten different hematologic disorders were identified according to the WHO-EORTC classifications: lymphomatoid papulosis (10 cases), mycosis fungoides (6 cases), anaplastic large cell lymphoma (4 cases), pre-B acute lymphoid leukemia (5 cases), primary cutaneous marginal zone B-cell lymphoma (4 cases), primary cutaneous CD4 + medium T-cell lymphoproliferative disorder (1 case), extranodal NK/T-cell lymphoma (1 case), hydroa vacciniforme-like lymphoproliferative disorder (1 case), B-cell lymphoblastic lymphoma (1 case) and acute myeloid leukemia (3 cases). Conclusion: The most common subtype of cutaneous hematologic disease in our single institution study was lymphomatoid papulosis (type A and type C), followed by mycosis fungoides. Recognition of this large clinical and histological spectrum by dermatologists is important because diagnosis is often established by biopsy of skin lesions, even in secondary cutaneous cases. Moreover, the clinicopathological correlation is of utmost importance for the final diagnosis of those pathologies.